PROFIL PENDERITA KANKER PAYUDARA STADIUM LANJUT BAIK LOKAL MAUPUN METASTASIS JAUH DI RSUP HASAN SADIKIN BANDUNG - Mochamad Aleq Sander (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2011)
Breast cancer represent one of the most second malignancy of the woman after cervix cancer. In Indonesia estimated ±100 new case per 100.000 population every year, meaning more or less 200.000 new case every year to all cancer type. While for the breast cancer ± 23.140 new case every year. If breast cancer found in early stage, it has high life expectancy, ranging from 85-95%. But actually 70-90% patient came to hospital after their disease were hard and advanced stage. Cancer medication at advanced stage was very difficult and its result very dissatisfactory. The aim of research is to know the epidemiology, clinical symptom, diagnosis, therapy, prognosis. Descriptive study with retrospective design. Total sampling was all outpatient in oncology deparment of Hasan Sadikin Hospital of Bandung with advanced stadium of breast cancer from January 2003 up to December 2008. 164 eligible respondens who had age below 35 yo 28 (17.1%) and above 35 yo 136 (82.9%). Average of menarche 11.77 yo. Location of right breast cancer 78 (47.6%), left 82 (50%), and both 4 (2.4%). A lot of stadium was T4bNoMx that is 18 (11%). Chest x-ray, laboratory, and USG were the most diagnostic procedure often used that is 19 (11.6%). The most common therapy was BE+VC+RM that is 17 (10.4%). The prognosis was healing 20 (12.2%), not/not yet healed 30 (18.3%), not control 110 (67.1%), and who control in the other place 4 (2.4%). Conclusion was mostly diagnosis of breast cancer according to anatomy pathology, chest x-ray, laboratory, and ultrasonografi. A lot of breast cancer location was left side. Excision biopsy, and followed by radical mastectomy were the most therapy procedure. Therapy evaluation to assess the level of healing was difficult because most patient did not conduct the control after therapy.